Immunotherapy for extensive-stage small-cell lung cancer: current landscape and future perspectives - Zhang, Shuang; Cheng, Ying (Frontiers in Oncology, 2023)
Small-cell lung cancer (SCLC) is a fatal subtype of lung cancer characterized by high aggressiveness, poor prognosis, and limited treatment options. For the first time in more than three decades, it has been demonstrated that the addition of immunotherapy to chemotherapy improved the survival of patients with extensive-stage SCLC, thereby immunotherapy plus chemotherapy established a new standard of first-line treatment. However, it is important to improve the curative effect of immunotherapy on SCLC and identify the patients who could benefit from such treatment. In this article, we review the current status of the first-line immunotherapy, the strategies to improve the efficacy of immunotherapy and the discovery of potential predictive biomarkers of immunotherapy for SCLC.